Revenue Management Perspectives in Small-Farm Winery Operations - Kulesza, Marie G. (Journal of Applied Business and Economics, 2021)
This exploratory multiple case study illustrates how revenue management decisions of small-farm winery owners may contribute to business sustainability in a regulated industry through the lens of dynamic capabilities. Given small-farm winery owners focus on brand development and customer base growth to sustain long-term survival, the findings of this study highlight the connection of revenue management tenets to pricing and inventory decisions to sustain full capacity and maximize revenue. Furthermore, the results indicate that small-farm winery owners’ revenue management strategic decisions may be influenced by resource and regulatory constraints and competitors’ impact on pricing and distribution tactics.